Enhancement of Antioxidant and Colon Anticancer Activity from Fermented Rice Bran Extract - Faizah Faizah; Adanti Wido Paramadini (Sean Institute, 2023)
This review focuses on the enhancement of antioxidant activity and the colon anticancer effect of fermented rice bran extract. Fermentation is a biological process that has been proven to significantly increase the content of bioactive compounds in various food sources, including rice bran. This study investigates how fermentation affects the antioxidant activity and colon anticancer potential of rice bran extract. The review highlights a positive correlation between phenolic content and antioxidant activity, indicating that fermented rice bran extract exhibits higher antioxidant properties compared to non-fermented ones. Additionally, this research explores the role of different fermentation microorganisms in promoting the release of phenolic compounds, contributing to increased antioxidant activity and colon anticancer effects. Understanding the potential health benefits of fermented rice bran extract can contribute to the development of functional food products with improved nutritional and therapeutic effects